2015
DOI: 10.1111/all.12539
|View full text |Cite
|
Sign up to set email alerts
|

Challenge-proven aspirin hypersensitivity in children with chronic spontaneous urticaria

Abstract: Nearly a quarter of children and adolescents with CSU were hypersensitive to aspirin. For children with chronic urticaria, determination of NSAID hypersensitivity in a well-controlled clinical setting will help to avoid severe drug hypersensitivity reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
0
24
0
1
Order By: Relevance
“…This phenotype was previously defined as 'aspirin-exacerbated cutaneous disease' (AECD) [38] , which is now known as NECD [10] . In our previous study, in which AECD was defined in a group of children and adolescents with CSU, 1 of the children exhibited bronchospasm upon the administration of aspirin during an OPT, although all the other participants had apparent angioedema and/or exacerbation of urticarial lesions [24] . Respiratory involvement may be a feature of NSAID-hypersensitive children with concurrent CSU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenotype was previously defined as 'aspirin-exacerbated cutaneous disease' (AECD) [38] , which is now known as NECD [10] . In our previous study, in which AECD was defined in a group of children and adolescents with CSU, 1 of the children exhibited bronchospasm upon the administration of aspirin during an OPT, although all the other participants had apparent angioedema and/or exacerbation of urticarial lesions [24] . Respiratory involvement may be a feature of NSAID-hypersensitive children with concurrent CSU.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were followed up for 6 h after the end of the OPTs. The patients and their parents were informed about the symptoms of a positive OPT and after the 6-hour follow-up period they were advised to call and readmit for an additional 48 h in the event of the occurrence of possible allergic symptoms, as previously described [24] .…”
Section: Opts With Nsaidsmentioning
confidence: 99%
“…Acute urticaria is more prevalent than chronic urticaria; however, chronic urticaria has a more significant impact on quality of life due to recurrence and unknown etiology 1. As in adults, the causes are different between acute and chronic urticaria in children,2345678 and it is difficult to determine the exact prevalence of childhood urticaria due to lack of papulation-based studies.…”
mentioning
confidence: 99%
“…In recent studies, more than 30% of children with chronic urticaria are classified as chronic autoimmune urticaria 56. Even though the prevalence is lower in children than in adults, nonsteroidal anti-inflammatory drugs are identified as major aggravating factors of chronic spontaneous urticaria in children 78. In the very recent studies of adults with chronic urticaria, serum vitamin D levels were likely to be lower and showed significant negative associations with urticaria activity score and duration 910.…”
mentioning
confidence: 99%
“…Nonsteroidal anti-inflammatory drugs (NSAIDs), penicillin and sulfonamide may cause chronic urticaria. One recent study found the NSAIDs and chronic urticaria in children and reported that 10% to 24% children with chronic urticaria have aspirin hypersensitivity [15].…”
Section: Drugsmentioning
confidence: 99%